Heat shock protein HSPA13 promotes hepatocellular carcinoma progression by stabilizing TANK - Xuesong Cen; Yuyan Lu; Jing Lu; Changhong Luo; Ping Zhan; Yizhe Cheng; Fan Yang; Chengrong Xie; Zhenyu Yin; Fuqiang Wang (Cell Death Discovery, 2023)
Abstract HSPA13, an important member of the heat shock protein family, plays an essential role in the oncogenesis of many organs, but the mechanism and function in hepatocellular carcinoma (HCC) is still unclear. In the present study, we found that HSPA13 was highly expressed in HCC and predicted poor clinical prognosis. Upregulation of HSPA13 was significantly associated with vascular invasion in HCC patients. Functionally, knockdown experiments demonstrated that HSPA13 promoted HCC proliferation, migration, and invasion. Mechanistic investigation showed that HSPA13 could interact with TANK to inhibit its ubiquitination and degradation. In addition, the expression of HSPA13 and TANK were positively correlated in HCC tissues. To conclude, the present study uncovers the oncogenic function of HSPA13 in the progression of HCC by regulating the stability of TANK. These findings suggest that HSPA13 and TANK may serve as promising targets for the diagnosis and treatment of HCC.